Nuclear envelope budding and its cellular functions. Issue 1 (31st December 2023) - Keuenhof, Katharina S.; Kohler, Verena; Broeskamp, Filomena; Panagaki, Dimitra; Speese, Sean D.; Büttner, Sabrina; Höög, Johanna L.
ABSTRACT: The nuclear pore complex (NPC) has long been assumed to be the sole route across the nuclear envelope, and under normal homeostatic conditions it is indeed the main mechanism of nucleo-cytoplasmic transport. However, it has also been known that e.g. herpesviruses cross the nuclear envelope utilizing a pathway entitled nuclear egress or envelopment/de-envelopment. Despite this, a thread of observations suggests that mechanisms similar to viral egress may be transiently used also in healthy cells. It has since been proposed that mechanisms like nuclear envelope budding (NEB) can facilitate the transport of RNA granules, aggregated proteins, inner nuclear membrane proteins, and mis-assembled NPCs. Herein, we will summarize the known roles of NEB as a physiological and intrinsic cellular feature and highlight the many unanswered questions surrounding these intriguing nuclear events.